Analisis Eksperimental dan Statistik Pengaruh Tekanan Udara dan Massa Benda Kerja terhadap Kecepatan Silinder Pneumatik pada Sistem Produksi Modular - Hendry Sakke Tira; Mulyadi Mulyadi; I Gusti Ngurah Ketut Yudhyadi (CV. IRA PUBLISHING, 2026)
Industrial automation systems widely employ pneumatic actuators; however, most existing studies focus on control strategies or isolated actuator components, with limited experimental validation in integrated automation platforms and insufficient evaluation of fundamental parameters such as supply pressure and load mass. This gap restricts a comprehensive understanding of actuator performance under realistic conditions. This study aims to experimentally and statistically evaluate the effects of air pressure and workpiece mass on pneumatic actuator performance in a Modular Production System (MPS) distributing station. A full factorial design (3 × 3) was used, with three levels of air pressure (3, 5, and 7 bar), three levels of workpiece mass (106, 112, and 118 g), and three repetitions per condition (27 runs). Cylinder speed was determined from the measured airflow rate, and statistical analysis was performed using one-way ANOVA. The results show that air pressure has a significant effect on cylinder speed (p < 0.05), with a 165% increase from 3 bar to 7 bar. In contrast, workpiece mass variation does not significantly affect cylinder speed (p > 0.05). These findings indicate that actuator performance in modular pneumatic systems is primarily governed by pressure-induced airflow. The study provides experimentally validated insights for improving system performance through effective pressure regulation.